Fast handover control scheme for multi‐node using the group‐based approach. Issue 1 (1st January 2015) - Chiang, Meng‐Shu; Huang, Chung‐Ming; Tuan, Dao Duy
Abstract : The fast handover Mobile IPv6 (FMIPv6) offers a handover preparation mechanism for a mobile node (MN) to reduce the handover latency over wireless network. However, FMIPv6 mainly deals with one MN instead of multiple MNs. In the wireless network, a group of MNs may move from the same previous network to the next network. In this paper, a group‐based fast handover (GB‐FH) control scheme is proposed to resolve the aforementioned problem. For the proposed GB‐FH scheme, one MN initiates a handover preparation and other neighboring MNs can join the handover preparation using the "hitch‐and‐ride" concept, which means that when one MN is preparing for a handover, its neighbours can join the on‐going handover preparation. Through the use of the shared invocation of the handover preparation procedure, (1) the handover preparation delay and handover latency can be reduced for about 20% and 8% respectively comparing with FMIPv6, (2) handover control messages can be reduced for about 57% comparing with FMIPv6 and (3) the contention of the wireless channel for multiple MNs can be improved due to the use of fewer control messages.